Juridical Analysis of Artificial Intelligence-Based Patient Personal Data Protection - Vera Dumonda Silitonga; Sidhi Laksono (Institute of Computer Science (IOCS), 2024)
Confidentiality of patient personal data is also a patient's right which is regulated in Law number 29 of 2004 and Law number 44 of 2009. Along with the development of technology, some loopholes can be exploited by cybercrime perpetrators. in general, they use malware programs to hack the target's computer system. The Information and Electronic Transactions Law (UU ITE) articles 30 and 31 regulate illegal access to systems belonging to other people or the public. Articles 32 and 34 also regulate illegal access and transactions with electronic documents owned by other people or the public. Violators can be charged using article 48 of the ITE Law. To date, no law specifically regulates the crime of hacking using malware on artificial intelligence technology used in hospitals. This research method is normative juridical with descriptive research methods. The specific legal basis (lex specialis) that regulates the protection of patient personal data concerning the illegal buying and selling of patient data (information business and electronic technology) that uses AI does not yet exist in the law, the closest thing is Article 67 of the Personal Data Protection Law in a general context. In this case, it can result in a legal vacuum, legal uncertainty or uncertainty about statutory regulations, or legal chaos.